2021
DOI: 10.54435/heos.v1i4.28
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use among University Students in Malaysia during the COVID-19 Pandemic

Abstract: Social media tools for communication, such as Twitter, Facebook, Instagram, or YouTube, have become important with the development of information and communication technology. In the field of higher education, university students are increasingly using social media to study and live. Consequently, university students and social media use have become a research topic of practical significance. Scholars in Malaysia have investigated this issue, and the results abound. However, few scholars have reviewed the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Yet, academic performance is a result of multi-dimensional causes, SM addiction may affect the level of depression, self-esteem and sleep quality, etc. leading to an academic performance downturn (Baturay & Toker, 2017;Busalim, 2019;Dongke & Sannusi, 2021). So as main findings of this study showed in the following contents.…”
Section: Mediation Analysis and Soble Testmentioning
confidence: 55%
“…Yet, academic performance is a result of multi-dimensional causes, SM addiction may affect the level of depression, self-esteem and sleep quality, etc. leading to an academic performance downturn (Baturay & Toker, 2017;Busalim, 2019;Dongke & Sannusi, 2021). So as main findings of this study showed in the following contents.…”
Section: Mediation Analysis and Soble Testmentioning
confidence: 55%
“…The influence from social media has shaped their self-worth to more appearance-based and desirability. In fact, research by Dongke and Shahrul Nazmi (2021) has indicated that social media usage had a significant impact on mental health of universities students, be it male or female. With fitness-related content becoming more relevant, as simple as diet or workout routines featuring muscular bodies, its existence of "ideal" body image is still embedded cognitively among social media users (James, 2021;Gutierrez, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study among college students in China showed that cyberbullying in social media and gaming contexts was associated with higher anxiety and internet addiction symptoms [ 28 ]. Among university students in Malaysia, social media use during the COVID-19 pandemic has been linked to depression and anxiety symptoms [ 29 ] and lower self-esteem [ 22 ].…”
Section: Introductionmentioning
confidence: 99%